2021
DOI: 10.1002/jcla.23953
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of circRNA hsa_circ_001888 in gastric cancer and its clinical significance

Abstract: Background Circular RNAs (circRNAs) are a novel family of endogenous RNAs. Recent studies have demonstrated that circRNAs are potential novel biomarkers for diagnosing cancers. However, little is known about the role of circRNAs in gastric cancer (GC). This study aimed to identify the relationship between GC and a new circRNA named hsa_circ_001888. Methods Hsa_circ_001888 expression levels were measured by quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR) in GC cell lines, tissues, and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…It also showed a significant effect in AFP-negative hepatocellular carcinoma. Shi et al (41) similarly found that low expression of plasmaderived hsa_circ_001888 in gastric cancer may be a potential diagnostic marker.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It also showed a significant effect in AFP-negative hepatocellular carcinoma. Shi et al (41) similarly found that low expression of plasmaderived hsa_circ_001888 in gastric cancer may be a potential diagnostic marker.…”
Section: Discussionmentioning
confidence: 98%
“…Shi et al. ( 41 ) similarly found that low expression of plasma-derived hsa_circ_001888 in gastric cancer may be a potential diagnostic marker.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs have high structural stability and tissue specificity and these characteristics provide the important foundation for circRNAs as cancer biomarkers 18 . For example, circ_001888 was abnormally expressed in gastric cancer and used as a probable diagnostic biomarker 19 . Circ_0010235 was identified as a closed-loop circRNA through the stability analysis using RNase R treatment and through the structure analysis using Oligo (dT) 18 primers.…”
Section: Discussionmentioning
confidence: 99%
“…Since circRNAs covalently bind the 5' and 3' ends of RNAs into a circular structure (21), circRNAs are considered to be more stable than miRNAs, mRNAs, and long noncoding RNAs (22). Given that circRNAs are widely present in body fluids, including plasma, serum, exosomes, and urine, they are a new biomarkers for monitoring cancer development and progression (9,10,23,24). To clarify the relationship between the abnormal expression of circRNAs and their prognostic value in gastric cancer patients, Chen et al searched articles reporting the relationship between circRNAs and the prognosis of gastric cancer through a meta-analysis (25).…”
Section: Discussionmentioning
confidence: 99%
“…Their unique circular structure results in their high stability. circRNAs commonly exist in various human body fluids and exosomes, offering the potential of using circRNAs as biomarkers of gastric cancer (9,10). Many researchers have elucidated the multiple functions of circRNAs, such as competitively binding to proteins and microRNAs (miRNAs), participating in protein coding, and regulating gene transcription (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%